2015
DOI: 10.1016/j.resuscitation.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Causes of in-hospital cardiac arrest – Incidences and rate of recognition

Abstract: Various cardiac and hypoxic aetiologies dominated. In two-thirds of IHCA episodes, the underlying cause was correctly identified by the ET, i.e. according to the findings of the aetiology study group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
75
3
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(103 citation statements)
references
References 26 publications
12
75
3
13
Order By: Relevance
“…19,20 In many IHCA studies the proportion of witnessed/observed cardiac arrests has been as high as 85-92% and it has been discussed, that previous IHCA studies represent poorly the actual patient population on general wards because of the high proportion of ICU/emergency department/cardiac care unit patients. 9,20,21 Brindley et al excluded patients allocated to 'critical care units' and found that 58% of the IHCAs were witnessed/observed, which is in line with our findings. 19 Still, two thirds of patients experiencing a witnessed/observed cardiac arrest on general wards is rather high.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…19,20 In many IHCA studies the proportion of witnessed/observed cardiac arrests has been as high as 85-92% and it has been discussed, that previous IHCA studies represent poorly the actual patient population on general wards because of the high proportion of ICU/emergency department/cardiac care unit patients. 9,20,21 Brindley et al excluded patients allocated to 'critical care units' and found that 58% of the IHCAs were witnessed/observed, which is in line with our findings. 19 Still, two thirds of patients experiencing a witnessed/observed cardiac arrest on general wards is rather high.…”
Section: Discussionsupporting
confidence: 91%
“…Cardiac causes were still more common than non-cardiac causes, however approximately 10% less prevalent than reported in studies including all hospital departments. 9,10 Of the specific causes of IHCAs, acute myocardial infarction and myocardial ischaemia without later findings of infarction together accounted for 35% of the arrests. This finding is of utmost importance, considering that only 15% of all general ward IHCAs had a shockable primary rhythm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hypoxemia and acidosis typically contribute to persistent or recurrent pulseless electrical activity during prolonged cardiac arrest, although hypoxemia may cause almost 25% of arrests attributed to pulseless electrical activity. 65,66,68,69 The pulse rate and QRS width on ECG can provide useful clues in regard to the cause of nontraumatic pulseless electrical activity (Figure 1). 62 Reversible causes (pseudopulseless electrical activity from profound shock) often produce tachycardia with visible P waves and a narrow QRS complex (tachycardic pulseless electrical activity with a supraventricular rhythm).…”
Section: Interventionsmentioning
confidence: 99%